A Custom-Made Surgical Guide for Accurate Enucleation of Nasopalatine Duct Cysts: A Technical Note and Case Report - Masako Fujioka-Kobayashi; Naoki Miyasaka; Ayako Miyasaka; Masateru Koyanagi; Ryo Inada; Takahiro Miyasaka; Takafumi Satomi (Case Reports in Dentistry)
Nasopalatine cysts are common nonodontogenic cysts that occur in the maxilla. During the nucleation of large cysts extending to the floor of the nasal cavity, care must be taken to avoid damage to the nasal mucosa. In the present report, an innovative custom-made surgical guide made by a Three-dimensional printer is introduced for accurate enucleation surgery. The patient’s cone-beam computerized tomography and dental model scan data were obtained, and a tooth-supported type of surgical guide was designed containing a circular plate structure showing the size of the cystic region, an indicator that showed the position of the bottom of the cyst, and a sliding stopper that was used to accurately indicate the position of the deepest cyst wall. The surgical tool enabled us to indicate the accurate size, location of the cysts, and approach direction. Although effective and accurate navigation systems have become increasingly available, the cost-effective and accurate computer-aided design/computer-aided manufacturing surgical guide system introduced in the present report could support the safe enucleation of large nasopalatine duct cysts.